An objective global climatology of polar lows based on reanalysis data. (18th October 2018) - Stoll, Patrick J.; Graversen, Rune G.; Noer, Gunnar; Hodges, Kevin
Abstract : Here we present an objective global climatology of polar lows. In order to obtain objective detection criteria, the efficacy of several parameters for separating polar lows from other cyclones has been compared. The comparison and the climatology are based on the ERA‐Interim reanalysis from 1979 to 2016 and the high‐resolution Arctic System Reanalysis from 2000 to 2012. The most effective parameters in separating polar lows from other extratropical cyclones were found to be the difference between the sea‐level pressure at the centre of the low and its surroundings, the difference in the potential temperature between the sea surface and the 500 hPa level, and the tropopause wind speed poleward of the system. Other parameters often used to identify polar lows, such as the 10 m wind speed and the temperature difference between the sea surface and the 700 hPa level, were found to be less effective. The climatologies reveal that polar lows occur in all marine basins at high latitudes, but with high occurrence density in the vicinity of the sea‐ice edge and coastal zones. The regions showing the highest degree of polar‐low activity are the Denmark Strait and the Nordic Seas, especially for the most intense polar lows. In the North Atlantic and Pacific, the main polar‐low season ranges from November to March. In the Southern Hemisphere, polar lows are mainly detected between 50 and 65°S from April to October, indicating that this hemisphere compared to its northern counterpart has a two months longer, but less intense, polar‐low season. No significant hemispheric long‐term trends are observed, although some regions, such as the Denmark Strait and the Nordic Seas, experience significant downward and upward trends in polar lows, respectively, over the last decades. For intense polar lows, a significant declining trend has been observed for the Northern Hemisphere. Abstract : Polar lows are intense mesoscale cyclones developing in the winter season over oceans at high latitudes. In this study, the efficacy of several parameters for polar detection are compared and the most effective criteria are applied for the derivation of an objective global climatology of polar lows. The average spatial distribution of polar‐low activity is presented in the figure, revealing the Nordic Seas and the Denmark Strait as most active regions.